Diagnostic evaluation of a high-sensitivity troponin I point-of-care assay - Sörensen, Nils A.; Neumann, Johannes T.; Ojeda, Francisco; Giannitsis, Evangelos; Spanuth, Eberhard; Blankenberg, Stefan; Westermann, Dirk; Zeller, Tanja (Clinical chemistry, 2019)
BACKGROUND: Increasing numbers of patients are presenting worldwide to emergency departments with suspected myocardial infarction. The use of point-of-care troponin assays might enable faster decision-making in this high-risk population and reduce the burden on emergency facilities. Here, we evaluate the diagnostic performance of a point-of-care high-sensitivity troponin I assay. - METHODS: We conducted a prospective cohort study including patients presenting to the emergency department with suspected myocardial infarction from July 2013 to July 2016. A diagnostic algorithm for a high-sensitivity troponin I point-of-care assay was developed in a derivation data set with 669 patients and validated in an additional 610 patients. - RESULTS: The derived 0/1 h algorithm for the point-of-care assay consisted of an admission troponin I <4 ng/L and a δ from 0 h to 1 h <3 ng/L for rule out and an admission troponin I ≥90 ng/L or a δ from 0 h to 1 h ≥20 ng/L for rule in of non-ST-elevation myocardial infarction. Application to the validation cohort showed a negative predictive value of 99.7% (95% CI, 98.1%-100.0%) and 48.0% of patients ruled out, whereas 14.6% were ruled in with a positive predictive value of 86.5% (95% CI, 77.6%-92.8%). The diagnostic performance of the point-of-care high-sensitivity assay was highly comparable to guideline-recommended use of a laboratory-based high-sensitivity troponin assay. - CONCLUSIONS: The clinical application of a 0/1 h diagnostic algorithm based on a high-sensitivity troponin I point-of-care assay is safe, and diagnostic performance is comparable to a laboratory-based high-sensitivity troponin I assay.
Gesehen am 14.01.2020